Crianças negras em escolas de “alma branca” : um estudo sobre a diferença étnico-racial na educação infantil - Souza, Edmacy Quirina de (2016)
Usually we come across quite discriminatory realities, in which black children live a subjectivity that sees and absorbs their identity in a negative and subaltern way. This leads us to believe that we are subjectivated in a particular order – the normative order – and according to a bleaching culture. This work – Black children in schools of “white soul”: a study on ethnic/racial differences in early childhood education – constitutes a survey that aims to analyze how the child, as a culturally constructed individual, experience ethnic/racial differences in the context of early childhood education and investigates how these differences constitute the organization of educational spaces and discursive and non-discursive practices produced by children and teachers, enabling to understand how we came to be who we are in relation to race and color. So we ask ourselves: how the spaces and environments, the imagery, discursive and disciplinary practices reveal the racial issue? The race and ethnicity categories in childhood enable to understand the power relations, the classifications and the hierarchizations on subjective constructions of the young individuals and allow thinking about the white, black, yellow and indigenous children present in our schools. The concepts of race, ethnicity and childhood are based on Cultural Studies and some of Foucault's perceptions, with emphasis on the relationship between knowledge and power, on issues related to the difference and on the discursive productions, which have significantly contributed to the incorporation of new research objects, including topics on the racial, sexual and gender diversity, among others. In this discussion we will analyze images produced by educational institutions in which speeches of bleaching and Eurocentric culture valorization are propagated. Subsequently, we will contemplate the speeches produced by the children and teachers when exposed to the images shown in the schools‟ geographical area. The speeches produced by the images, the children and the teachers fabricate a truth about the racial diversity, the black child and the bleaching. These standings help to reaffirm the supposed superiority of the white person over the black person. However, a work within this perspective of otherness runs away from the essentialist research, which often seek a universal truth and the normativity of the subject. Therefore, it can be seen as a work which explores new routes, becoming capable of finding new territories.